Social work bachelor students’ knowledge awareness during field practice: Student’s perspectives (Journal of Comparative Social Work, 2020)
Social work has increasingly become a research-based discipline, while at the same time acknowledging the importance of knowledge gained through practical experience and user knowledge. Awareness of various forms of knowledge becomes particularly relevant to practice as it constitutes a framework for understanding and addressing social problems in real-life situations. This article presents findings from a Q methodological study exploring social work bachelor students’ perspectives on knowledge after taking part in research-oriented activities during field practice placement in Norwegian welfare organizations. The aim of the study was to explore how bachelor students of social work understand and find knowledge useful to social work practice. Q methodology aims at revealing shared perspectives, and facilitates comparison between perspectives. Three perspectives on knowledge emerged from the study. The first emphasizes the importance of combining experience-based knowledge and research-based knowledge. The second suggests an orientation towards research-based knowledge as a strategy for innovation, while the third focuses on an active and confident, yet critical, use of research-based knowledge when working with service users. Field placements as arenas for enhancing students’ knowledge awareness, and bridging various forms of knowledge, are discussed in light of these findings.